Historical Dictionary of Methodism - Yrigoyen, Charles, Jr.; Warrick, Susan E. (Lanham : Scarecrow Press, 2013)
This third edition of Historical Dictionary of Methodism presents the history of Methodism through a detailed chronology, an introductory essay, an extensive bibliography, and over 500 cross-referenced dictionary entries on important institutions and events, doctrines and activities, and especially persons who have contributed to the church and also broader society in the three centuries since it was founded. This book is an ideal access point for students, researchers, or anyone interested in the history of the Methodist Churc.
Editor's Foreword; Preface; Acronyms and Abbreviations; Chronology; Introduction; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y; Z; Bibliography; About the Contributors.
Includes bibliographical references.
Description based on print version record.
Keywords: Methodist Church -- Dictionaries; Methodists -- Biography -- Dictionaries; Methodism; Methodist church -- Dictionaries; Methodists -- Biography -- Dictionaries; RELIGION / Christianity / Methodist; Electronic books